Genetic studies on high lignan content in sesamum (Sesamum indicum L.): Genetic studies on high lignan content in sesamum (Sesamum indicum L.) - S MD USMAN; P L VISWANATHAN; S MANONMANI; D UMA (Journal of Oilseeds Research, 2020)
Lignans especially sesamin and sesamolin are secondary metabolites having therapeutic value. The sesame germplasm were screened for lignan content. A set of four low lignan and four high lignan lines were crossed in Line x Tester mating design. Based on the evaluation of F1s, the genotype KRISHNA was identified as good combiner and the cross (JLS 57 x PKDS 12) showed high sca effects. The crosses (JLS-57 x GUN-18), (KRISHNA x GUN- 18), (JLS 57 x PKDS 12) and (KRISHNA x PKDS-12) showed high heterosis for yield and lignan content.